MiPyme En el Giro Industrial : Factores de Competencia - Siller, Jesús Francisco Mellado; Ruiz, Edith Reyes; Wong, Adriana Méndez (European Scientific Journal, ESJ, 2017)
The present study aims to determine which of the factors that considers the industrial small and medium enterprises. It makes them feel that they are better than their competitors. For this purpose, a factorial analysis of the variables was applied. These are findings which show that only two are the main factors in the industry. First, it involves what is related to internal marketing in terms of efficient processes, satisfied employees, and companies that have good performance and which are more profitable. Second, it also entails what concerns competitiveness. Here, we have the items of higher quality products, customer satisfaction, and adaptation to market changes that improves their intangible value.